Effect of choline supplementation on fatigue in trained cyclists - Spector, S. A.; Jackman, M. R.; Sabounjian, L. A.; Sakkas, C.; Landers, D. M.; Willis, W. T. (Medicine & Science in Sports & Exercise, 1995)
Preliminary research suggested that depletion of choline (the neuromuscular transmitter) may limit performance and that oral supplementation may delay fatigue during prolonged efforts. In this investigation the relationships between plasma choline and fatigue during supramaximal brief and submaximal prolonged activities were determined. Healthy males who trained more than 124 km/wk were randomly assigned to a brief (N = 10; > 150% VO2max) and prolonged (N = 10; 70% VO2max) work group. Each group performed two trials, one after choline supplementation and the other after drinking a placebo. One hour after drinking choline bitartrate increases in plasma choline (37-52%) were observed. Neither group depleted choline during either the choline supplement or placebo conditions. Fatigue times and work performed were similar under both conditions in each group. It was concluded that choline was not depleted in either condition nor did choline supplementation delay fatigue. Implication. In the Ss used in this study and for the types of exercise performed, choline was not depleted and its supplementation had no effect on performance or onset of fatigue.